(untitled) (Acta Entomológica Chilena, 2022)
An inventory of beetles of the Wildlife Sanctuary “Península of Hualpén”, an important biogeographic area in the Bio-Bio Región of Chile, was carried out in order to characterize the taxonomic composition of Coleóptera. A data base based on published research, sporadic samples and material of reference collections was made. The beetle fauna of the sanctuary is represented by 20 families, 60 genera and 76 species. The most di verse families were Curculionidae, Tenebrionidae, Chrysomelidae, Cerambycidae and Carabidae, whereas Cleridae, Melyridae, Mordellidae, Staphylinidae and Zopheridae were very scarcely represented. More studies are needed in Península of Hualpén to obtain a better characterization of Coleóptera, in order to establish a biodiversity knowledge necessary to propose protection measures against the growing human pressure.